Control in the field of environmental protection and rational (sustainable) use of natural resources in the context of environmental support for economic and other activities (legal aspect) - Moroz, Oleg V. (Journal of the Belarusian State University. Law, 2026)
The legal content of the control in the field of environmental protection and the rational (sustainable) use of natural resources makes it possible to conclude that it constitutes an established element of environmental support for economic and other activities, implemented at the stage where project and other decisions are carried out. Certain characteristics of its legal forms are provided. A flexible legal approach is observed in selecting an entity subject to a selective inspection. However, there is no guaranteed conduct of such inspections for entities engaged in environmentally hazardous activities. The article highlights the specific features of objects of control in the field of environmental protection and rational (sustainable) use of natural resources, which are not limited solely to the economic and other activities of entities, since control is aimed at ensuring compliance with environmental legislation as a whole. Recommendations are formulated to improve the legal regulation of environmental relations.
Keywords: control; state bodies (organisations); inspection; field activities; environmental protection; economic and other activities